EASL and AASLD recommendations for the diagnosis of HCC to the test of daily practice. (26th April 2017) - Aubé, Christophe; Oberti, Frédéric; Lonjon, Julie; Pageaux, Georges; Seror, Olivier; N'Kontchou, Giséle; Rode, Agnes; Radenne, Sylvie; Cassinotto, Christophe; Vergniol, Julien; Bricault, Ivan; Leroy, Vincent; et al.
Abstract: Aims: To evaluate the diagnostic performance of CT, MRI and CEUS alone and in combination, for the diagnosis of HCC between 10 and 30 mm, in a large population of cirrhotic patients. Patients and methods: In a multicentre prospective trial, 442 patients have been enrolled. Within a month, CEUS, CT and MRI were performed for all patients. A composite algorithm was defined to obtain the more accurate gold standard. Results: A total of 544 nodules in 381 patients have been retained for the performance analysis. Eighty‐two percent of the patients were male, mean age was 62 years. For the 10‐20 mm nodules (n=342), the sensitivity (Se) and specificity (Sp) for the diagnosis of HCC were, respectively, 70.6% and 83.2% for MRI, 67.9% and 76.8% for CT and 39.6% and 92.9% for CEUS. For the 20‐30 mm nodules (n=202), the Se and Sp were, respectively, 72.3% and 89.4% for MRI, 71.6% and 93.6% for CT and 52.9% and 91.5% for CEUS. The best combination for the 10‐20 mm nodules was MRI + CT (Se: 55.1%, Sp: 100.0%): After a first inconclusive technique, CEUS as second image technique allowed the highest specificity with only a slight drop of sensitivity for 10‐20 mm nodules and the highest sensitivity and specificity for 20‐30 mm nodules. Conclusion: This large multicentre study validates the EASL/AASLD recommendations in daily practice. Specificity using CT or MRI in 10‐20 mm HCC was low, but we do not recommend combined imaging at first as sensitivity would be very low. The best sequential approach combined MRI and CEUS.